Serbian family households in respect to rural tourism development - Jelić, Sreten; Gligić Dumonjić, Jovana; Kuzman, Boris (Economics of Agriculture, 2010)
In this paper is given relation between rural household and rural tourism. Serbia has numerous resources for rural tourism development. Involvement of households, economic and no economic activities which have interest in rural tourism development, tourism should become one of the most important generators of rural development and therefore overall economic activities. Resources of family households in Serbia are signifcant and enable their members to participate in touristic activities also. Family households in rural areas can produce healthy food which is important part of rural tourism development.